2016
DOI: 10.1186/s40634-016-0070-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing the effectiveness of the ultrasound-guided galvanic electrolysis technique (USGET) versus conventional electro-physiotherapeutic treatment on patellar tendinopathy

Abstract: BackgroundPatellar tendinopathy has a high prevalence rate among athletes. Different therapeutic options can be found in the current literature, but none of them has been clearly established as the gold standard. The purpose of this study is to compare, in a randomized controlled trial, the clinical efficacy of eccentric exercise combined with either an ultrasound-guided galvanic electrolysis technique (USGET) or conventional electrophysiotherapy to treat patellar tendinopathy.MethodsSixty patients diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 27 publications
1
53
0
4
Order By: Relevance
“…Three studies by the same author group 1-3 reported good results of EPI in terms of clinical improvement. A prospective case series 1 showed a significant improvement of VISA, and all patients returned to their preinjury level of physical activity at 2-year follow-up.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Three studies by the same author group 1-3 reported good results of EPI in terms of clinical improvement. A prospective case series 1 showed a significant improvement of VISA, and all patients returned to their preinjury level of physical activity at 2-year follow-up.…”
Section: Resultsmentioning
confidence: 98%
“…Another prospective case series 2 reported a significant improvement of clinical scores and a satisfaction rate of 97.5% at 120 months’ of follow-up. The most recent study 3 was an RCT comparing EPI with a treatment protocol that consisted of pulsed ultrasound, laser CO 2 , and interferential currents; the authors reported better results in the EPI group in terms of clinical improvement and success probability (72.4% vs 36.1%) at 2 months’ follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…9 Physical therapy approaches continue to evolve and include the combination of DN and electrolysis, known as percutaneous needle electrolysis (PNE), with promising results for the treatment of tendon pathologies. [16][17][18] The PNE technique is a minimally invasive treatment that consists of the application of a galvanic electrolytic current that causes a controlled local inflammatory process in the target tissue. This promotes phagocytosis and the subsequent regeneration of the affected tissue.…”
Section: Open Accessmentioning
confidence: 99%
“…Therefore, current results should be considered in the investigated scenario. Finally, the application of percutaneous electrolysis is usually ultrasound-guided [ 16 , 17 , 18 , 19 , 20 , 21 ]. In the current study, the technique was not ultrasound-guided, which could have influenced the results.…”
Section: Discussionmentioning
confidence: 99%